2021
DOI: 10.1186/s12245-020-00322-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of retropharyngeal hematoma by trans-arterial embolism without intubation

Abstract: Background Retropharyngeal hematoma can cause suffocation if there is delay in securing the airway by intubation. However, there are also concerns about complications that can arise with intubation; it is still unknown which cases do not require intubation. Case presentation An 88-year-old woman slipped and was found prone and was transported to the emergency room. She was alert without any stridor. Physical examination revealed a subcutaneous hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In previous studies, tracheotomy was performed within four days in all the patients evaluated. [7,17] Some studies used follow-up imaging or direct observation of the hematoma by laryngoscopy to decide whether to perform tracheotomy [12,18,20]. The present study showed that more than 40% of patients needed to be transferred to other hospitals for rehabilitation.…”
Section: Clinical Implementationmentioning
confidence: 71%
See 2 more Smart Citations
“…In previous studies, tracheotomy was performed within four days in all the patients evaluated. [7,17] Some studies used follow-up imaging or direct observation of the hematoma by laryngoscopy to decide whether to perform tracheotomy [12,18,20]. The present study showed that more than 40% of patients needed to be transferred to other hospitals for rehabilitation.…”
Section: Clinical Implementationmentioning
confidence: 71%
“…In previous studies, tracheotomy was performed within four days in all the patients evaluated. [ 7 , 17 ] Some studies used follow-up imaging or direct observation of the hematoma by laryngoscopy to decide whether to perform tracheotomy [ 12 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because hematoma formation leads to airway obstruction, tracheal intubation should be considered [1,4]. In previous reports, some patients did not require intubation [3,5]. Still, others required intubation five to 20 hours after admission, often when patients did not need intubation at presentation to the emergency department [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reports of VA injury as a possible source of RH [8,9]. Sugiura et al introduced seven cases of RH for which conventional angiography was performed [10]. In 6 cases, transarterial embolization was effective in controlling retropharyngeal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%